PENGARUH PEMBERIAN PUPUK KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT GAHARU (Aquilaria spp.) - Heriyanto '; M. Mardhiansyah '; Rudianda Sulaeman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research was to determine the effect of compost fertilizer of oil palm empty bunch are mixed with top soil as a growing medium to promote growth and development of gaharu. This research is completely randomized experimental design (CRD), which consists of 4 treatment and 10 replicates, number of plants was 40. he treatments are: A0 = Without TKKS Compost, A1 = 25% TKKS Compost + 75% top soil, A2 = 50% TKKS Compost + 50% top soil, A3 = 75% TKKS Compost + 25% top soil. Based on the results of this research can be concluded that fertilization with compost of oil palm empty bunch are mixed with top soil as a growing medium for seedlings of gaharu able to provide a complete nutrient, so the growth and development of gaharu for the better. The Treatment fertilizing with compost Tankos 75% were mixed with 25% top soil is a treatment that is able to give effect to the high growth of seedlings of gaharu which amounted to 5.08 cm, diameter growth of seedlings of gaharu which is equal to 0.15 mm and dry weight of the plant which amounted to 2.03 g. Keywords: Compost Tankos, Top Soil, Seeds of Gaharu